Determinasi Integritas Laporan Keuangan - Baihaqi, Muhammad Azhar; Praptiningsih, Praptiningsih (Accounting Student Research Journal, 2024)
Financial Statements are a form of corporate management responsibility aimed to stakeholders. The presentation of financial reports must be carried out accurately and free from misstatements in the preparation process. In other words, financial statements must have quality or integrity in its composition. The aim of this research is to determine the influence of company size, financial distress, independent commissioners, and public accounting firm size on the integrity of financial statements in infrastructure sector companies with profitability as a control variable. This research is quantitative research using secondary data from audited financial statements and company annual reports. Based on the results of the tests, it is concluded that 1) company size has no effect on the integrity of financial statements; 2) financial distress has no effect on the integrity of financial statements; 3) independent commissioners have a positive influence on the integrity of financial statements; 4) public accounting firm siz has a positive effect on the integrity of financial statements.